SKRINING AWAL AKTIVITAS ANTIBAKTERI DAN ANTIOKSIDAN EKSTRAK SEMUT (INSECTA: FORMICIDAE) DARI GARUT - JAWA BARAT - Efendy, Oscar; Fathoni, Ahmad; Praptiwi, Praptiwi; Royyani, Mohammad Fathi; Wulansari, Dewi; Agusta, Andria (BERITA BIOLOGI, 2019)
Studies on the therapeutic use of insects and insect products have been neglected compared to the use of other animals or plants.This study aims to determine the antibacterial and antioxidant potential of ants extracts. Preliminary study related to antibacterial and antioxidant screeningof 17 extracts of ant colonies that belongs to 8 species were performed by Thin Layer Chromatography (TLC)-Bioautography. Antioxidant activity was measured by DPPH free radical scavenging method. The antibacterial activity was done against three pathogenic bacteria, i.e Bacillus subtilis InaCC B-1, Staphylococcus aureus InaCC B-4 and Escherichia coli InaCC B-5 were performed by non-eluted TLC-autobiography assay. The minimum inhibitory concentration (MIC) and IC50 values of DPPH radical scavenging activity of active extracts were determined by microdilution in 96-well microplate. The results showed 6 extracts active against B.subtilis, 5 extracts active against S.aureus. The lowest MIC value was 512 µg/ ml.  Ten extracts had the antioxidant activity with various IC50 values. The extracts of ants might be used as bioactive resources for antibacterial and antioxidant.